ECOLOGICAL MODELING OF TALITROIDES TOPITOTUM (CRUSTACEA: AMPHIPODA) - Bueno Da Fonseca Lima, Ernesto Augusto [UNESP]; Matavelli, Cristane [UNESP]; Ferreira, Claudia Pio [UNESP]; Conde Godoy, Wesley Augusto (World Scientific Publ Co Pte Ltd, 2014)
A compartmental model was developed to describe the temporal course of an exotic amphipod's population, Talitroides topitotum, in an Atlantic Forest habitat in Brazil. Extensive biological information - including breeding pattern, development and mortality rates, and temperature dependence of the parameters - were considered in the model. A genetic algorithm was used to estimate model parameters by comparing simulation results with field data. This allowed us to discuss the reproductive strategies adopted by this species and to analyze the potential influence of global climate changes on its populations dynamics.
Keywords: Terrestrial Amphipod; Ordinary Differential Equation; Climate Changes; Atlantic Forest